Aggressive scrollers: investigating online aggression and its relationship with social media use, envy, self-control and aggressive behaviour - Sumarno, L.C. (2021)
Online Aggression, social media use, envy, self-control and trait aggression, what is the relationship? This thesis aimed to contribute some answers to this question. Social media and aggression are the main topics covered, this combination in recent years has been shown to be detrimental to individuals and society with ‘online’ aggression on the increase. The other more recent concern is the influence of social media on other outcomes such as the experience of envy or ‘offline’ aggression, including the cross over between threats ‘online’ and acting them out ‘offline’. This thesis is an exploratory piece of work with the overall aim of investigating ‘online’ aggression, it’s similarities and differences with ‘offline’ aggression, and the different psychological constructs that may help to explain the phenomena.